2004
DOI: 10.1152/ajpgi.00080.2004
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin-releasing peptide is a modulatory neurotransmitter of the descending phase of the peristaltic reflex

Abstract: Grider, John R. Gastrin-releasing peptide is a modulatory neurotransmitter of the descending phase of the peristaltic reflex. Am J Physiol Gastrointest Liver Physiol 287: G1109 -G1115, 2004. First published August 5, 2004; doi:10.1152/ajpgi.00080.2004.-The physiological role of gastrin-releasing peptide (GRP) and of its cognate receptors in regulating the intestinal peristaltic reflex was examined in a threecompartment flat-sheet preparation of rat colon. Mucosal stimulation applied to the central compartment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
(100 reference statements)
0
10
0
Order By: Relevance
“…In the case of the BB 1 receptor such areas include involvement in thyroid function and alterations in thyroid disease Pazos-Moura et al, 2003;Oliveira et al, 2006), behavior effects in mediating aspects of fear, anxiety, and stress responses Merali et al, 2002Merali et al, , 2006Yamada et al, 2003;Bédard et al, 2007); and satiety effects (Merali et al, 1999;Ladenheim and Knipp, 2007). For the BB 2 receptor, such areas include its role in motility with mediation of the descending peristaltic reflex (Grider, 2004) its role in lung injury and development of lung diseases, particularly neonatal lung disease and bronchopulmonary dysplasia, in which Bn-like peptides and the BB 2 receptor were shown to play an important role in various animal models (Li et al, 1994;Sunday et al, 1998;Emanuel et al, 1999;Cullen et al, 2000;Ashour et al, 2006;Ganter and Pittet, 2006;Subramaniam et al, 2007), its role in sepsis and in small intestinal mucosal protection and prevention of injury (Assimakopoulos et al, 2004(Assimakopoulos et al, , 2005aDal-Pizzol et al, 2006;Higuchi et al, 2006;Kimura et al, 2006a,b), its role in satiety effects (Merali et al, 1999;Ladenheim and Knipp, 2007), and its CNS effects on memory, learning, various behaviors, and response to stress (Merali et al, 1999(Merali et al, , 2006Yegen, 2003;Moody and Merali, 2004;Roesler et al, 2004Roesler et al, , 2006ados Santos Dantas et al, 2006;Luft et al, 2006Presti-Torres et al, 2007. For the BB 3 receptor such areas include its possible role in lung development and responses t...…”
Section: Therapeutic Implications Of Bombesin Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the BB 1 receptor such areas include involvement in thyroid function and alterations in thyroid disease Pazos-Moura et al, 2003;Oliveira et al, 2006), behavior effects in mediating aspects of fear, anxiety, and stress responses Merali et al, 2002Merali et al, , 2006Yamada et al, 2003;Bédard et al, 2007); and satiety effects (Merali et al, 1999;Ladenheim and Knipp, 2007). For the BB 2 receptor, such areas include its role in motility with mediation of the descending peristaltic reflex (Grider, 2004) its role in lung injury and development of lung diseases, particularly neonatal lung disease and bronchopulmonary dysplasia, in which Bn-like peptides and the BB 2 receptor were shown to play an important role in various animal models (Li et al, 1994;Sunday et al, 1998;Emanuel et al, 1999;Cullen et al, 2000;Ashour et al, 2006;Ganter and Pittet, 2006;Subramaniam et al, 2007), its role in sepsis and in small intestinal mucosal protection and prevention of injury (Assimakopoulos et al, 2004(Assimakopoulos et al, , 2005aDal-Pizzol et al, 2006;Higuchi et al, 2006;Kimura et al, 2006a,b), its role in satiety effects (Merali et al, 1999;Ladenheim and Knipp, 2007), and its CNS effects on memory, learning, various behaviors, and response to stress (Merali et al, 1999(Merali et al, , 2006Yegen, 2003;Moody and Merali, 2004;Roesler et al, 2004Roesler et al, , 2006ados Santos Dantas et al, 2006;Luft et al, 2006Presti-Torres et al, 2007. For the BB 3 receptor such areas include its possible role in lung development and responses t...…”
Section: Therapeutic Implications Of Bombesin Receptorsmentioning
confidence: 99%
“…GRP stimulates smooth muscle contraction in both the gastrointestinal tract and urogenital system and has profound effects on GI motility, stimulates release of numerous gastrointestinal hormones/neurotransmitters, stimulates secretion and/or hormone release from the pancreas, stomach, colon, and numerous endocrine organs, has potent effects on immune cells (macrophages, dendritic cells, lymphocytes, and leukocytes) (Ruff et al, 1985;De la Fuente et al, 1991van Tol et al, 1993;Plaisanci é et al, 1998;Makarenkova et al, 2003), has potent growth effects on both normal tissues and tumors; has potent CNS effects, including regulation of circadian rhythm, thermoregulation; regulation of anxiety and the fear response, regulation of food intake, and behavioral effects and is involved in mediating numerous CNS effects on the GI tract (Tache et al, 1988;Bunnett, 1994;Martinez and Tache, 2000;Jensen et al, 2001;Jensen, 2003;Grider, 2004;Jensen and Moody, 2006). In many tissues the effects of NMB overlap with those of GRP; however, NMB has specific effects in some tissues such as contraction of smooth muscle, growth effects in various tissues (Moody et al, 2000;Matusiak et al, 2005), CNS effects including effects on feeding, thermoregulation; regulation of TSH release, stimulation of various CNS neurons, behavioral effects; and effects on spinal sensory transmission (von Schrenck et al, 1989;Rettori et al, 1992;Ladenheim et al, 1997b;Ohki-Hamazaki, 2000;Merali et al, 2006;Oliveira et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Note also the presence of BRS-3-LI in a Syn-LI varicose nerve trunk innervating the circular muscle layer (arrowheads). Bar 50 μm the peristaltic reflex (Grider 2004). Furthermore, intracellular recordings of myenteric neurons from the guineapig ileum have revealed that bombesin-related peptides stimulate slow excitatory synaptic excitation; these effects are consistent with a neurotransmitter and/or a neuromodulatory function of the peptides (Zafirov et al 1985).…”
Section: Discussionmentioning
confidence: 91%
“…Part of this is associated with the diabetic autonomic neuropathy [32] . Intrathecal administration of is reported to induce integrated gastric response to food, which included vegally mediated contractions, while its role in peristalsis has been reported [13,21,33,34].…”
Section: Small Intestinementioning
confidence: 99%
“…GRP has been reported to be a potent, dosedependent arteriolar vasodilator and bronchoconstrictor in the guinea pig in vivo, although the mechanism of its action is not known [11,12] . In the GIT, it is reported to be selectively released from sub mucosal neurons in descending pathways during the peristaltic reflex [13] . It had also been reported to induce gall bladder contraction, partly by direct action on the smooth muscles of the gall bladder and partly by gastrin release [14] .…”
Section: Introductionmentioning
confidence: 99%